MANAJEMEN DANA BANTUAN OPERASIONAL SEKOLAH PADA SEKOLAH MENENGAH PERTAMA NEGERI 3 SAMBAS - Fahmi, Urai Riza (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract. This study aims to describe: (a) planning funds; (b) the organization of funds; (c) implementation of the funds; (d) the supervision of the fund managenent og BOS finds committed in SMP Negeri 3 Sambas. This study usesqualitative techniques of interview, and documentary studies. The type of data using observation extension, increase endurance, triangulation, discussions with colleagues and check. The results of this study are: (1) Planning BOS funds realized in the form of Plan and Budget Activity School (RKAS) are arranged based on the needs of the school within one year. (2) The organization in the management and disbursement of BOS is also contrary to the guidelines number 161 in 2014. (3) The use of BOS funds are not all used to plan and budget activities such as school fees are planned for one year. (4) The fungction of supervision in theÂ  management of BOS funds have not been up done iether by internal or external oversight institutions. Keywords: School Operational Asistance Fund Management